Gestational age-specific neonatal morbidity among pregnancies complicated by advanced maternal age: a population-based retrospective cohort study - Valent, Amy M (J Matern Fetal Neonatal Med, 2015)
OBJECTIVE: Compare significant neonatal morbidity frequency differences in advanced maternal age (AMA) versus non-AMA pregnancies, assessing which gestational week is associated with the lowest morbidity risk. METHODS: Population-based retrospective cohort study. Adverse neonatal outcome frequency differences were stratified by each week of gestation. Multivariate logistic regression estimated the relative risk (RR) of composite neonatal morbidity for women ages 35–39, 40–44, 45–49, and 50–55 vs. 18–34 years, adjusted sequentially for relevant risk factors. RESULTS: Neonatal morbidity decreased with each advancing week of term gestation, lowest at 39 weeks for all groups. Adverse neonatal outcome risk for births to AMA women increased at 40 weeks: 35–39 years (adj)RR 1.12 [1.01–1.24], ≥40 years 1.24 [1.01–1.52]. Each older maternal age category had increased risk for overall neonatal morbidity: 35–39 years (adj)RR 1.11 [95% CI 1.08–1.15], 40–44 years 1.21 [95% CI 1.14–1.29], and 45–49 years 1.34 [95% CI 1.05–1.69]. CONCLUSIONS: Lowest neonatal morbidity risk is at 39 weeks gestation with a significantly increased risk observed thereafter, especially in women ≥40 years.